ANALISIS PENGETAHUAN SUFIKS DERIVASI PEMBENTUK NOMINA DAN ADJEKTIVA MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JERMAN UNIVERSITAS PATTIMURA - Tahya, Chrisyo; Akihary, Wilma; Serpara, Henderika (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2024)
This qualitative research using descriptive analysis techniques aims to find out students' knowledge about suffixes forming nouns and adjectives and how the modification of suffix derivation forms nouns and adjectives. The sample of this research is in the form of test results from 19 students who have taken the Microlinguistics course. The results of this study are (1) Suffixes -e, -er, -keit, -schaft, -ung, -tät, -ion, -nis, -chen as noun formers in German are not well mastered by students of German Language Education Study Program. The average mastery of noun-forming suffixes is only 48%. The use of the suffix -e is the most (63%), while the use of the suffix -schaft is the least (37%) chosen by students as noun formers. While the average mastery of adjective marker suffixes -los, -bar, -ig, -sam, -lich, -al is only 47% with the suffix -los occupying the highest choice (63%) as an adjective marker suffix, and the suffix -al occupies the lowest choice (31%) in forming adjectives. (2) In the analysis of derivation modification, it is found that the modification of verb-derived derivation into nouns and adjectives is still poorly mastered by students.